Predictive value of the combination of SMAD4 expression and lymphocyte infiltration in malignant transformation of oral leukoplakia. (3rd March 2017) - Sakata, Junki; Yoshida, Ryoji; Matsuoka, Yuichiro; Nagata, Masashi; Hirosue, Akiyuki; Kawahara, Kenta; Nakamura, Takuya; Nakamoto, Masafumi; Hirayama, Masatoshi; Takahashi, Nozomu; Nakashima, Hikaru; Arita, Hidetaka; et al.
Abstract: Oral leukoplakia (OL) is a common, potentially malignant disorder of the oral cavity. SMAD4 was initially identified as a tumor suppressor and central mediator of transforming growth factor (TGF)‐ β signaling. In this study, we aimed to determine the expression patterns of SMAD4 in OL, its relationship with the degree of inflammation, and its clinical implications as a biomarker for OL malignant transformation. A total of 150 patients with OL were enrolled in this study. Paraffin‐embedded sections obtained from biopsy or resection specimens were subjected to immunohistochemical analysis. Associations among the status of epithelial SMAD4 expression, stromal lymphocyte infiltration, and malignant transformation of OL were examined. Malignant transformation was significantly associated with the status of SMAD4 expression ( P  =   0.0017) and lymphocyte infiltration status ( P  =   0.0054). Cox regression analysis, based on the event‐free survival (EFS), revealed that a low SMAD4 expression was a significant prognostic factor in OL patients (hazard ratio, 2.632; P  =   0.043). In addition, a low SMAD4 expression was closely correlated with high lymphocyte infiltration ( P  =   0.00035), resulting in a significant correlation between the combination of low SMAD4 expression and high lymphocyte infiltration with malignant transformation of OL ( P  =   0.00027). The combination of the status of epithelial SMAD4 expression and stromal lymphocyte infiltration may be a useful biomarker for predicting malignant transformation in OL patients. These results suggest that not only epithelial SMAD4 loss, but also stromal features, may regulate the risk of malignant transformation of OL. Abstract : SMAD4 loss in epithelial cells possibly contributes to changes in stromal features. SMAD4 may be a useful predictive marker for malignant transformation of oral leukoplakia.